PERANAN PENERAPAN PENDIDIKAN KARAKTER DI SEKOLAH TERHADAP PEMBENTUKAN KEPRIBADIAN PESERTA DIDIK - Rizka Amalia (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
Character education is an important component to form the learners’ personality especially in the school environment. The objective of character education in the school is to form the learners’ humanity or personal who are a good character, morality, and the spirit of social based on Pancasila values. Because of the reality, there are still many the crisis of the learners’ morality and characters in the school environment or the school outside such as smoking in the school area, fighting among learners, free sex, drug abuse, shameless culture, decency value that is slumped to older people especially parents , teachers and many others. Therefore, it is important to applied character education to the learners in the school so that learners can be attitude and act based on their personality values like a good character, morality and the spirit of social. And to support the realization of the success of implementation character education in the school, it should all elements like all the school residents, family and society to engage in its process.